Recent Trends on Mitigative Effect of Probiotics on Oxidative-Stress-Induced Gut Dysfunction in Broilers under Necrotic Enteritis Challenge: A Review - Obianwuna, Uchechukwu Edna; Agbai Kalu, Nenna; Wang, Jing; Zhang, Haijun; Qi, Guanghai; Qiu, Kai; Wu, Shugeng (Antioxidants, 2023)
Gut health includes normal intestinal physiology, complete intestinal epithelial barrier, efficient immune response, sustained inflammatory balance, healthy microbiota, high nutrient absorption efficiency, nutrient metabolism, and energy balance. One of the diseases that causes severe economic losses to farmers is necrotic enteritis, which occurs primarily in the gut and is associated with high mortality rate. Necrotic enteritis (NE) primarily damages the intestinal mucosa, thereby inducing intestinal inflammation and high immune response which diverts nutrients and energy needed for growth to response mediated effects. In the era of antibiotic ban, dietary interventions like microbial therapy (probiotics) to reduce inflammation, paracellular permeability, and promote gut homeostasis may be the best way to reduce broiler production losses. The current review highlights the severity effects of NE; intestinal inflammation, gut lesions, alteration of gut microbiota balance, cell apoptosis, reduced growth performance, and death. These negative effects are consequences of; disrupted intestinal barrier function and villi development, altered expression of tight junction proteins and protein structure, increased translocation of endotoxins and excessive stimulation of proinflammatory cytokines. We further explored the mechanisms by which probiotics mitigate NE challenge and restore the gut integrity of birds under disease stress; synthesis of metabolites and bacteriocins, competitive exclusion of pathogens, upregulation of tight junction proteins and adhesion molecules, increased secretion of intestinal secretory immunoglobulins and enzymes, reduction in pro-inflammatory cytokines and immune response and the increased production of anti-inflammatory cytokines and immune boost via the modulation of the TLR/NF-ĸ pathway. Furthermore, increased beneficial microbes in the gut microbiome improve nutrient utilization, host immunity, and energy metabolism. Probiotics along with biosecurity measures could mitigate the adverse effects of NE in broiler production.